UNIX network programming - Stevens, W. Richard (New Delhi PHI Learning, 1990)
A practical book that explains many of the details that have been considered a mystery, this guide book focuses on the design, development, and coding of networking software under the UNIX operating system. It begins by showing how a fundamental basic for networking programming in interprocess communication (IPC), and a requisite for understanding IPC is a knowledge of what constitutes a process. Throughout, the text provides both a description and examples of how and why a particular solution is arrived at
Appendix A.1-A.4, 720-734p.; Bibliography 735-747p.; Index 748-772p.
Keywords: Network programming; Computer science